Association between Growth Differentiation Factor-15 and Risk of Cardiovascular Diseases in Patients with Adult Growth Hormone Deficiency - Xun Wu; Yunting Wang; Ziyu Ren; Linman Li; Wenjie Qian; Yue Chen; Wei Ren (International Journal of Endocrinology)
Objective. Patients with adult growth hormone deficiency (AGHD) confer a heightened risk of cardiovascular disease and increased mortality because of metabolic disorders. Growth differentiation factor-15 (GDF-15) plays an important role in predicting metabolic abnormalities. We sought to investigate the correlation between GDF-15 and cardiovascular risk in AGHD patients. Methods. The study enrolled 80 AGHD patients and 80 healthy subjects. We analyzed the association between GDF-15 and some major biochemical indicators. The potential association between GDF-15 and cardiovascular disease risk was analyzed. Results. The AGHD group exhibited increased waist-hip ratio and high-sensitivity C-reactive protein (hs-CRP) and lipid levels compared with the healthy control group. Serum GDF-15 levels in AGHD group were elevated significantly compared with the control group P<0.001. GDF-15 levels were negatively associated with insulin-like growth factor-1 in AGHD group P=0.006 and positively correlated with waist-to-hip ratio P=0.018, triglycerides P=0.007, and hs-CRP P=0.046. In addition, GDF-15 was positively correlated with Framingham risk score significantly after adjustment for other factors (r = 0.497, P<0.001). Moreover, GDF-15 was an independent risk factor for cardiovascular disease in AGHD patients after adjusting for traditional cardiovascular risk factors. Conclusion. Elevated GDF-15 levels were significantly associated with cardiovascular risk factors and can be considered as a predictive biomarker of cardiovascular risk in AGHD patients.